The Development Of IPA Learning Module Based on Mind Mapping For Grade III SDN 33 Kinali Pasaman Barat - Aseb Yumiati; Gusnita Efrina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to produce teaching materials in the form of learning modules on theme 1, material on the growth and development of living things, sub-theme 1, characteristics of living things, for class III students at SDN 33 Kinali, West Pasaman Regency, which are valid, practical and effective. The type of research used is Research and Development (R&D) 4-D method, namely defining, designing, developing and disseminating. This research included a validation questionnaire sheet which was validated by 3 validators and a practicality sheet by 1 teacher and class III students at SDN 33 Kinali, West Pasaman Regency. The effectiveness test was the test results of class 33 Kinali students, West Pasaman Regency. The research results showed that the module produced was very valid by the validators with an average score (94.44%) for both material (83.69%), language aspects (100%), and design aspects (100%). The resulting module was suggested to be very practical by teachers with an average (100%), and was suggested to be very practical by students with an average (100%). The results of the research on the effectiveness test were considered very practical with an average of (100%). From the research results, it can be concluded that the development of an Indonesian language learning module based on Mind Mapping for class III students at SDN 33 Kinali, West Pasaman Regency that has been produced is very valid, very practical and effective so that it can be used in the science learning process in class III of elementary school